A consistent treatment of the boundary layer for atmospheric models. (12th October 2018) - Allen, Thomas; Zerroukat, Mohamed
Abstract : It is common to treat the parametrisation of the atmospheric boundary layer, as well as other physics packages, separately from the inviscid dynamics within weather/climate models. In the case of the boundary layer in particular, there is then an issue with the application of the boundary conditions which are different, such as no‐slip and free‐slip. This article proposes a consistent and tightly coupled approach that involves incorporating the boundary‐layer terms within the semi‐implicit treatment of the dynamics and resulting Helmholtz problem. Abstract : Cross‐section of the velocity components ( u, v, w ) after 1 day for a constant viscosity.